Microscopic and radiographic analysis of the effect of particle size of demineralized bovine cancellous bone matrix on the repair of bone defects in femurs of rabbits - Carneiro, Everdan (2005)
The bone tissue has a great regenerative potential, with ability to completely restore its structure and original functions. In some situations, though, bone defects cannot be self-repaired, thus requiring the use of grafts for a correct treatment and good prognosis. This work aimed at microscopically analyzing the effect of the particle size of demineralized bovine cancellous bone matrix in micro and macrogranular forms on the repair of bone defects in femurs of rabbits, with blood clot used as control. At 1, 3 and 6 months after implantation of the materials, the animals were killed and the anatomic specimens were removed. A foreign body-type granulomatous reaction containing macrophages and multinucleated giant cells in contact with the implanted particles was observed. These results suggest a failure in demineralization and/or interruption of the antigenic potential during production of the biomaterial. It is concluded that the size of the particles did not influence the evolution of the repair process of bone defects, acting only as bone-filler substances, and that the material implanted should be improved by quality control during production, since it may represent a good alternative for bone graft.